International Graduate Student Labor as Mergers and Acquisitions - Cantwell, Brendan; Lee, Jenny J.; Mlambo, Yeukai A. (Journal of International Students, 2018)
This study critically examines the self-reported experiences of international graduate students using a framework understanding internationalization as acquisitions and mergers. Students reported positive experiences with their advisors. However, students’ accounts of laboratories and other research settings were diverse, ranging from co-contributors to knowledge and respected collaborators to employed cheap labor that their advisors depended upon for their own gains. In some cases, these students feared that their funding would be cut off or dismissed from the program (and consequently deported from the US) if they challenged their advisors. Whether such apprehensions were valid is unknown as this study focused on perceptions of the students only. The findings do lead to important future directions for research and practice.